The role of HSP60 in Atherosclerotic Coronary Heart disease - Kadhim, Wurood A.S.; Mohaymen, Nidhal A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Heat shock proteins have a general role in the response of the arterial wall to stress and may serve as a mediator/inducer of atherosclerosis in particular circumstances when HSPs specifically bind to the Toll-like receptor 4/CD14 complex, initiating an innate immune response, including the production of pro-inflammatory cytokines, this also followed by cytokine amplification through transmigration of macrophages and neutrophils.Objective: To investigate the percentage of expression of HSP60 by peripheral blood lymphocyte (PBL) in atherosclerotic coronary heart disease (CHD) patients using immunocytochemistry technique.Method: A total of fifty patient (40 males and 10 females), ranged from the mean age (59.12±8.54) years with a range from 42-80 years and fifteen, age and sex matched, apparently healthy individuals, taken as a healthy control group, were enrolled in the current study and the patients group were further classified into acute cases (n=11 patients) ״7 males and 4 females״ and chronic cases (n=39 patients) ״33 males and 6 females״. Three ml of blood sample had been taken from each subject, and immediately transferred to sterile heparinised vacutainer tubes for lymphocyte separation. Immunocytochemistry was used to detect HSP60 by using monoclonal antibody to HSP60 protein.Result: Results revealed a statistically significant elevation levels between patients and control groups (P=0.000), the expression of HSP60 was elevated in all patients with no significant difference between acute and chronic cases (P>0.001).Conclusions: HSP60 plays an important role in induction and development of atherosclerosis by stimulating different mechanisms which are the triggers for the process of atherosclerosis development. It is found in higher levels in both acute and chronic cases of atherosclerotic CHD in comparison with control cases.